Simulation of productive processes using Lego® blocks for application of the concepts of integrated production management - Olivares, Gustavo Lopes; Ormond, Eduardo de Oliveira; Rangel, Raphaela Pereira (Brazilian Journal of Operations & Production Management, 2020)
Goal: This article describes a simulation exercise based on the premises of the experiential learning approach, using Lego® blocks to build a production plant model. Design / Methodology / Approach: The simulation was applied to groups of 4 to 6 participants, enrolled in production management or similar classes. Results: The use of this approach promoted a learning environment with greater interaction and stimulated the students to put their reasoning, decision-making and communication skills into practice. Limitations of the investigation: Because the simulation is only a representation of reality, it can generate some generalization, and since it is a controlled experiment, all the variables are known in advance. Therefore, the practices using the simulation should be discussed and contrasted with real-world practices after application of the method. Practical implications: This simulation enables examining themes such as inventories, supply chains, production planning and scheduling, layout, MRP, and mainly integration of organizational processes in practice, promoting hands-on experience. Originality / Value: The reports of the participants indicated a positive impact of the proposed simulation, by stimulating the development of skills and capabilities for their training as future managers.